Innovations in Electronics and Communication Engineering Proceedings of the 7th ICIECE 2018 - Saini, H. S.; Singh, R. K.; Kumar, Girish; Rather, G.M; Santhi, K. (Lecture Notes in Networks and Systems,, 2019)
This book gathers selected papers presented at the 7th International Conference on Innovations in Electronics and Communication Engineering, held at Guru Nanak Institutions in Hyderabad, India. It highlights contributions by researchers, technocrats and experts regarding the latest technologies in electronic and communication engineering, and addresses various aspects of communication engineering, including signal processing, VLSI design, embedded systems, wireless communications, and electronics and communications in general. Covering cutting-edge technologies, the book offers a valuable resource, especially for young researchers. .